Growing CAPITOL 4 Life: A Case Study of Co-designed Material for the First 1000 Days Using a Modified Double Diamond Approach - Andrew P. Hills; Sisitha Jayasinghe; Kylie Mulcahy; Kylie Burgess; Lisa Dalton; Kiran D. K. Ahuja; Roger Hughes; Nuala M. Byrne (Maternal and Child Health Journal, 2026)
Abstract Introduction Growing CAPITOL 4 Life is a place-based public health initiative focused on the first 1000 days (F1D), from conception to a child’s second birthday. It sought to strengthen community capacity for early-childhood health by leveraging local knowledge, assets and partnerships, while moving beyond one-way information provision towards sustained learning, empowerment and collective action. This study retrospectively examined the co-design process through the lens of the Double Diamond. Methods Parents, educators, service providers and community stakeholders across Burnie, Circular Head and Devonport, Tasmania, participated in co-design workshops. Engagement spanned government, local government, Aboriginal organizations, libraries and community services. The process was facilitated by a place-based systems-change organization and supported by the University of Tasmania. Community members contributed lived experience alongside professional and academic knowledge, with decision-making remaining largely community-led and guided by the principle of “for the community, by the community.” Results Across the four phases, communities moved from sharing experiences and identifying strengths and challenges (Discover), to refining priorities (Define), developing locally relevant resources and learning approaches (Develop), and shaping feasible delivery models (Deliver). The process centered on the F1D domains of Connection, Nutrition, Caring and Moving and resulted in community-informed Evidence Briefs, workshops and playgroup-based learning. Importantly, the Double Diamond was reflected not as a prescribed sequence, but as a recurring pattern of opening outward to explore and narrowing inward to make sense, prioritize and act. Discussions moved organically between what was working, what was missing, what an ideal future might look like and how communities could move towards it. Discussion The findings suggest that the value of the Double Diamond in public health lies less in adherence to predefined stages than in providing sufficient structure for purposeful exploration while preserving community agency. This flexible approach may support locally relevant, acceptable and trusted solutions, particularly in complex regional settings where effective public health responses must emerge from, rather than be imposed upon, communities.